PURIFICATION OF WASTE COOKING OIL USING ACTIVATED CARBON FROM SUGAR CANE BAGASSE AND H2SO4 ACTIVATOR - Mardwita, Mardwita; Yusmartini, Eka Sri; Rahayu, Meylinda; Elfidiah, Elfidiah (Barometer, 2023)
Waste cooking oil is one of the B3 wastes produced by industrial or household activities. Since this waste cooking oil will cause pollution to the environment, hence it cannot be disposed directly into the environment. Reuse of this cooking oil through a refining process is an alternative way to reduce the amount of waste cooking oil. This study aims to determine the effect of sulfuric acid (H2SO4) as an activator and the effect of contact time on water content, free fatty acid levels, and saponification levels. In this study, we used waste cooking oil that has been heated for 9 hours and 11 hours. The mass of activated carbon used was 7.5 gr, 12.5 gr and 14.5 gr, and the contact times were 9 hours, 120 hours and 144 hours. The results showed that the lowest water content was 47,81% achieved by waste cooking oil heated for 11 hours and 14,5 gr of activated carbon, whereas free fatty acid was reduced until 29,7% on waste cooking oil heated 9 hours and 14,5 gr of activated carbon.